Musical Analysis. Historia - Theoria - Praxis, Vol. 6, 2021 - Granat-Janki, Anna. Redakcja (Akademia Muzyczna im. Karola Lipińskiego we Wrocławiu, 2021)
This publication belongs to the series entitled Musical Analysis. Historia - Theoria - Praxis devoted to the analysis of a musical work, encompassing both the description of the structure and form of a composition, and the interpretation of music, which enables its understanding. Discovering meanings in music is an ever-present subject of interest for scholars all over the world. It is also part of a long-standing research tradition at the Chair of Music Theory and History of Silesian Musical Culture of the Karol Lipiński Academy of Music in Wrocław, where the series has been originated. The book contains texts by musicologists, music theoreticians, composers, conductors and music therapists from Poland and abroad. The research problems they examine include meaning and significance in music, narratology and music rhetoric, intertextuality and word music relations, representation in music, genre-related issues, the style of musical works, the usefulness of analysis in studying musical sources, and the concepts and methods of analysis. It is our belief that the book will arouse interest of a wide range of readers and enrich the knowledge of musical analysis and interpretation
Keywords: signification in music; narratology; intertextuality; methods of musical analysis; interpratation of sources; musical genology